Canberra population survey, September - October 1978: drug data file - Brewer, Ken R. (ADA Dataverse, 2018)
During an omnibus survey respondents were questioned concerning their use and frequency of use of alcohol, tobacco and other drugs including pain killers, stomach settlers, sedatives and tranquillisers. Marijuana use was investigated using a randomised response technique. Further questions involved the respondents' approval of changes to laws relating to marijuana use and supply. Background variables included age, education, qualifications and income.